Scaffolding technologies for the engineering of cultured meat: Towards a safe, sustainable, and scalable production. (August 2022) - Levi, Shira; Yen, Feng-Chun; Baruch, Limor; Machluf, Marcelle
Abstract: Background: Cultured meat aims to solve the current sustainability and environmental issues of conventional livestock husbandry by converging tissue engineering practices with food innovation science to recapitulate the components and structure of animal-derived meat. To this end, various scaffolding technologies were adopted and developed to support the cultivation, expansion, and differentiation of cells using edible, low-cost, and sustainable materials and methods. The cell-scaffold constructs can benefit different processing strategies that include structuring approaches and additives to generate final cultured meat products. Scope and approach: In this paper, we elaborate on the main considerations for the design of scaffolds for cultured meat applications, review the leading scaffolding technologies, and discuss their current or potential application for the engineering of cultured meat. Key findings and conclusions: The extensive research efforts in recent years attest to the boundless potential of novel cultured meat scaffolds. Moreover, different scaffolding technologies originally developed for tissue engineering can be adapted to cultured meat by using edible materials and avoiding toxic crosslinkers and reagents throughout all of the development steps, thus ensuring compliance with food and safety regulations. Altogether, the combination of tissue engineering and food science technologies holds the promise of technologically and commercially viable scaffolds towards the realization of the cultured meat vision. Graphical abstract: Image 1 Highlights: Cultured meat is produced in-vitro from animal cells cultured on scaffolds. Scaffolds for cultured meat should support cell attachment and proliferation. Cultured meat scaffolds need to be food-grade, low-cost, scalable, and sustainable. Diverse scaffolding technologies can be adapted from tissue engineering to cultured meat.